KEWIRAUSAHAAN SOSIAL PADA LEMBAGA ZAKAT NASIONAL BERKANTOR PUSAT DI SURABAYA - Akmalur Rijal; Muhammad Nafik Hadi Ryandono; Tika Widiastuti (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
Social entrepreneurship is one solution that can be applied to channel aid continuously and even empower the poor. Amil zakat institutions are developing social entrepreneurship activities to add their institution's source of income as inputs to be channeled to needy communities. This study aims to determine the form of social entrepreneurship within the national zakat institution and to know the role of social entrepreneurship in supporting the activities of social activities of national zakat institutions headquartered in Surabaya. This research takes the location of research at four national zakat institutions headquartered in Surabaya, namely Yayasan Dana Sosial al-Falah (YDSF), Nurul Hayat, Yatim Mandiri, and Lembaga Manajemen Infaq (LMI). This study uses a case study approach as part of qualitative research. The results of this study are (1) LAZNAS with head office in Surabaya doing social entrepreneurship activity with two forms that is establishment of business unit first then running social activity and forming social unit first then running business unit. (2) The business unit run by the zakat institution in Surabaya is able to support the operational of the social activities it undertakes. (3) Social entrepreneurship applied by zakat institution in surabaya proven able to support social activities run by national zakat institution having head office in Surabaya